Foil is an acronym of First Outer Inner Last. This is used to find out the product of two terms. In this method, first we have to multiply the first term with the first term of the second bracket then multiply the first term in the first bracket with the second term in the second bracket. Next we have to multiply both terms in the second bracket with second term in the first bracket. Add all these values to get the solution. For better understanding, let us see the given figure.

Related Calculators | |

Foil Calculator | Acceleration Formula Calculator |

Area of a Circle Formula Calculator | Area of a Cylinder Formula Calculator |

Solved problems related to foil method are given below:

### Solved Examples

**Question 1: **Evaluate (2x+4)(5x+3) ?

** Solution: **

Given function is, (2x + 4) (5x + 3)

According to foil formula,

(2x + 4) (5x + 3) = (2x * 5x + 2x * 3) + (4 * 5x + 4 * 3)

(2x + 4) (5x + 3) = 10$x^{2}$ + 6x + 20x + 12

(2x + 4) (5x + 3) = 10$x^{2}$ + 26x + 12

**Question 2: **Evaluate (3x-1)(x+5) ?

** Solution: **

Given function is, (3x - 1)(x + 5)

According to foil formula,

(3x - 1) (x + 5) = (3x * x + 3x * 5) + (-1 * x - 1 * 5)

(3x - 1) (x + 5) = 3$x^{2}$ + 15x - x - 5

(3x - 1) (x + 5) = 3$x^{2}$ + 14x - 5

Given function is, (2x + 4) (5x + 3)

According to foil formula,

(2x + 4) (5x + 3) = (2x * 5x + 2x * 3) + (4 * 5x + 4 * 3)

(2x + 4) (5x + 3) = 10$x^{2}$ + 6x + 20x + 12

(2x + 4) (5x + 3) = 10$x^{2}$ + 26x + 12

Given function is, (3x - 1)(x + 5)

According to foil formula,

(3x - 1) (x + 5) = (3x * x + 3x * 5) + (-1 * x - 1 * 5)

(3x - 1) (x + 5) = 3$x^{2}$ + 15x - x - 5

(3x - 1) (x + 5) = 3$x^{2}$ + 14x - 5